The Role of Schools in Local Communities and the Ecological-Systems Approach to Addressing Bullying in the Local Environment - Bučar Ručman, Aleš (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
School is one of the key institutions in the local community. In addition to education, it provides socialisation, social control, the transmission of values, and the reinforcement of dominant ideology. In the context of peer bullying, there is often a misconception that schools should resolve such issues independently. Violence is an overly complex phenomenon shaped by factors at multiple levels – from individual characteristics to family and peer relationships, as well as broader social structures and global influences. Effective responses require an ecological-systems approach and a proper understanding of violence. Successful prevention is based on collaboration among schools, local communities and various local structures (clubs, associations), experts, and the state. The state must ensure evidence-based violence prevention programs, staff training, and specialised support teams.